Marine power distribution system fault location using a portable injection unit - Jia, Ke; Bi, Tianshu; Liu, Bohan; Christopher, Edward; Thomas, David W.P.; Sumner, M. (IEEE, 2015)
A portable injection unit for Active Impedance Estimation (AIE) is built and tested in a DC zonal marine power distribution system to provide useful information for system protection and restoration. The portable unit generates current “spikes” and injects them into the system once short circuit faults are detected (by measuring the system voltage drop). The faulted system impedance can be estimated by AIE and comparing the estimated impedance with the pre-calibrated value, the fault location can be determined. The proposed method does not rely on system fault transient information or communication from the remote-end measurement and offers fast and accurate fault location in DC marine distribution systems. The proposed method has been tested and validated on a 750V, 2 MW twin bus DC Commercial Test Facility with the system both de-energised and energised.